Cosmeto-textiles - Singh, Mukesh Kumar; Singh, Annika; Morris, Holly Victoria (Textile progress, 2023)
Cosmeto-textiles are textiles that aim to enrich and address aspects of modern-day life, such as slimming by cellulite reduction, skin moisture management, energising the human body, protection from ultraviolet radiation, providing pleasant fragrance or providing anti-ageing-appearance properties. To achieve the intended outcomes, various compounds of animal, mineral, and plant origin are utilised in cosmeto-textiles and incorporated into the textile product. Cosmetic functionality can be incorporated into textiles by modifying the fibre by introducing a functional moiety into the fibre’s polymer chain, or by doping the polymer with additives before fibre extrusion, by functionalising the yarns, or by coating the fabrics or garments for example by grafting or lamination. This is commonly undertaken by the use of microencapsulation or using cyclodextrin as a cage material. The cosmeto-textiles market is expanding globally. Whilst characterisation of cosmeto-textiles has been challenging, the Europeans have taken the lead in classifying and standardising the testing of cosmetic effects of cosmeto-textiles in the same manner that cosmetic items are tested. Cosmeto-textiles may be characterised by the chemical attributes they have or by the function they undertake. Whilst the field of cosmeto-textiles remains at an embryological stage, the joint efforts of cosmetic scientists, textile engineers, biochemists, dermatologists, and life scientists are allowing for standardisation of testing and an expansion in products that can be taken through to market. This issue of Textile Progress aims to summarise the field as it currently stands.